2009
DOI: 10.1177/1545109709336221
|View full text |Cite
|
Sign up to set email alerts
|

Known to Be Positive But Not in Care: A Pilot Study From Thailand

Abstract: This study was designed to describe persons with HIV/ AIDS (PWHAs) in Thailand who have not disclosed their HIV status to the government HIV clinics to receive medical care. Objectives were to (1) demonstrate a way to access these persons, and (2) describe their characteristics, HIV status, reasons for nondisclosure, and problems related to their self-care. Two nongovernmental organizations (NGOs) serving the nonmedical needs of PWHAs were used. In all, 22 PWHAs participated. Approximately 80% have known their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…2 The previous article suggested that these individuals could be identified and contacted through NGOs serving HIV-positive persons and by referral from other HIV-positive individuals. 1 This study demonstrated the value of reaching out to nondisclosed HIV-infected persons. It showed that gaining the trust of these persons and assisting them with their everyday problems and consistently meeting, counseling, and educating them could create significant changes in their lives including engaging in HIV care.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…2 The previous article suggested that these individuals could be identified and contacted through NGOs serving HIV-positive persons and by referral from other HIV-positive individuals. 1 This study demonstrated the value of reaching out to nondisclosed HIV-infected persons. It showed that gaining the trust of these persons and assisting them with their everyday problems and consistently meeting, counseling, and educating them could create significant changes in their lives including engaging in HIV care.…”
Section: Discussionmentioning
confidence: 67%
“…The demographic characteristics of the patients were described in the previous article. 1 The first research question for the current study, would these N-PWHAs remain in contact with the researcher for an extended period of time, was answered positively. The nurse researcher was able to meet with the N-PWHAs 2 to 3 times per month for at least 6 months.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Others cannot imagine that they have any risk for HIV infection because they believe they have not engaged in risk behavior. 23,24 Past campaigns to increase knowledge, understanding, and concern for prevention of new HIV infection in the general population and for those with higher risk is one measure that may have contributed to the success of the Thai government in preventing the AIDS epidemic from being worse than it could have been. But these public information campaigns have decreased significantly in the past decade, as the focus has shifted to prevention of drug abuse.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…28 Stigma has been identified in Thailand. 23,[29][30][31][32] Thailand was one of the first countries in Asia to make ART available without charge to its HIV-infected population. 26,33 As a result, there are now a significant number of HIV-infected persons who have survived to adolescence and to young adulthood in Thailand.…”
Section: Settingmentioning
confidence: 99%